Formulation of Malaysian clay into inert ceramic balls : Effect of sintering temperature - Fikri Hakim, Zainudin; Muhammad Shafiq, Zulkifli; Anisah Sajidah, Haji Saud; Salim, Nurjannah; Hanafi, Ani; Anwaruddin, Hisyam; Edy Sutjipto, Agus Geter; Mohd Hasbi, Ab Rahim (Elsevier Ltd, 2023)
Ceramic ball support bed materials are used in multiple industries with the aim of providing support for the catalytic materials and assisting the reaction. The majority of ceramic ball products used in Malaysia are either imported as finished products or domestically produced using an imported formulated powder. Besides, the characteristics of sintered ceramic balls depend on the specific powder metallurgy route, including the material composition, range of particle size, and sintering process. Thus, this study focuses on producing inert ceramic balls from local Malaysian raw materials and optimising the sintering temperature with the aim of fulfilling the Universal Oil Products (UOP) standard requirements. The research utilises local clay raw material originating from Trong, Perak, Malaysia. The formulation of each ball was formulated based on a mixture of kaolinite clay, potash feldspar, and silica sand. The sintering process was then varied between 1250 and 1350 °C to tune the character of the finished ceramic ball product. The characterization of the ceramic ball was carried out based on the UOP standard and complemented with X-ray Diffractometer (XRD), Scanning Electron Microscope – Energy Dispersive X-ray (SEM-EDX), and X-ray Fluorescence (XRF) analysis. All tested ceramic balls meet the requirements of the UOP standard. In fact, locally formulated samples had approximately twice the crushing strength of required standards. Different sintering temperatures affect the quartz phase, kaolinite dehydroxylation, mullite formation, and feldspar fusion, thus controlling the final physical–mechanical properties of ceramic balls. Overall, the sintering temperature of 1300 °C provides the most promising output in terms of the quality of ceramic balls and the cost consideration involving the high-temperature heating process.